miR-144-3p Suppresses Osteogenic Differentiation of BMSCs from Patients with Aplastic Anemia through Repression of TET2 - Li, Ning (Mol Ther Nucleic Acids, 2019)
Reduced osteogenic capacity of bone marrow mesenchymal stem cells (BMSCs) has been causally linked to the development of aplastic anemia. In this work, we aimed to identify novel microRNAs (miRNAs) that participate in the regulation of differentiation of BMSCs from patients with aplastic anemia. We show that miR-144-3p is significantly upregulated in BMSCs from patients with aplastic anemia relative to control equivalents. Depletion of miR-144-3p significantly enhances osteogenic differentiation of BMSCs from patients with aplastic anemia after culturing in osteogenesis-inducing medium. Conversely, overexpression of miR-144-3p blocks osteogenic differentiation of BMSCs. Mechanistically, miR-144-3p negatively regulates the expression of ten-eleven translocation 2 (TET2) in BMSCs. Reduced TET2 expression is associated with a significant decrease in global 5-hydroxymethyl-cytosine (5hmC) levels and osteogenic gene expression. Knockdown of miR-144-3p elevates the expression of TET2 and total 5hmC levels in BMSCs. Silencing of TET2 inhibits the osteogenic differentiation of BMSCs. Overexpression of TET2 reverses miR-144-3p-mediated inhibition of osteogenesis. In addition, there is a significant negative correlation between the expression of miR-144-3p and TET2 in BMSCs from patients with aplastic anemia. Overall, miR-144-3p impairs the osteogenic capacity of BMSCs from patients with aplastic anemia through repression of TET2. Therefore, the targeting of miR-144-3p may be a therapeutic strategy against aplastic anemia.